Influence of diet patterns on time of emergence of permanent teeth of children of Quetta, Pakistan - Nazeer Khan; Mujeeb ur Rehman Baloch; Hasham Khan; Arham Chohan; Sarfraz Ali Abbasi (Khyber Medical University Journal)
OBJECTIVE: To determine the effect of meat, vegetable, rice, and milk on the emergence of permanent teeth in children from Quetta city of Baluchistan province of Pakistan.